Cryogenic operation of NanoBridge at 4 K for controlling qubit. (1st May 2022) - Okamoto, Koichiro; Tanaka, Takahisa; Miyamura, Makoto; Ishikuro, Hiroki; Uchida, Ken; Sakamoto, Toshitsugu; Tada, Munehiro
Abstract: A nonvolatile resistive switching of NanoBridge TM (NB) at 4 K has been demonstrated for realizing the Quantum-classical interface (QCI), in which the challenging of reset operation at cryogenic temperature is successfully achieved. The set voltage of the NB is increased with decreasing temperature, saturated around 150 K and to be 2.55 V at 4 K. The on-state resistances tuned at 1 k–5 kΩ show small temperature dependence down to 4 K due to high residual resistivity. The increased reset current of the NB at 4 K is compensated by the process optimization with thermal engineering and the increased I dsat of the select transistor at 4 K, resulting in stable switching. The low-power QCI featuring NBs is a strong candidate for controlling a large number of qubits at cryogenic temperature.